Characterization, functional properties, and resistant starch of freshwater macrophytes - Syed, Nurul Nur Farahin; Zakaria @ Ya, Muta Harah; Bujang, Japar Sidik; Christianus, Annie (Hindawi Publishing, 2021)
Several aquatic macrophytes such as Colocasia esculenta, Eleocharis dulcis, Nelumbo nucifera, Sagittaria sagittifolia, Trapa bispinosa, and Typha angustifolia possessed carbohydrate mainly in their storage and reproductive parts. Starch morphology, total starch, and amylose content of these six freshwater plant species were determined. Their functional properties, i.e., starch crystallinity, thermal properties, and rheological behaviour were assessed. Large starch granules were in N. nucifera rhizome (>15 μm), medium-sized was N. nucifera seed (8-18 μm), while the rest of the starches were small starch granules (<8 μm). Shapes of the starch granules varied from oval and irregular with centric hilum to elongated granules with the eccentric hilum. Eleocharis dulcis corm starch had significantly higher total starch content (90.87%), followed by corms of C. esculenta (82.35%) and S. sagittifolia (71.71%). Nelumbo nucifera seed starch had significantly higher amylose content (71.45%), followed by T. angustifolia pollen (36.47%). In comparison, the waxy starch was in N. nucifera rhizome (7.63%), T. bispinosa seed (8.83%), C. esculenta corm (10.61%), and T. angustifolia rhizome (13.51%). Higher resistant starch was observed mostly in rhizomes of N. nucifera (39.34%)>T. angustifolia (37.19%) and corm parts of E. dulcis (37.41%)>S. sagittifolia (35.09%) compared to seed and pollen starches. The XRD profiles of macrophytes starches displayed in all the corms and N. nucifera seed had A-type crystallinity. The T. bispinosa seed had CA-type, whereas the rest of the starches exhibited CB-type crystallinity. Waxy starches of C. esculenta corm had higher relative crystallinity (36.91%) and viscosity (46.2 mPa s) than regular starches. Based on thermal properties, high-amylose of N. nucifera seed and T. angustifolia pollen resulted in higher gelatinization enthalpy (19.93 and 18.66 J g-1, respectively). Starch properties showed equally good potential as commercial starches in starch-based food production based on their starch properties and functionality.